In vivo evaluation of wound healing improvement of a new Schiff base derived bromine compound (CNBP) in rats - Saremi, Kamelia; Bagheri, Elham; Rad, Sima Kianpour; Salman, Abbas Abdulameer; Majid, Nazia Abdul (Elsevier, 2019)
Background: The effect of delivered bromine vapor and also bromine substitutions are shown to play an important role in anti-inflammatory activity. The present study encompasses a broad in vivo study to size up healing activity of a novel dibromide substituted Schiff based compound against cutaneous wound model in Sprague Dawley (SD) rats. Methodology/principal findings: 2, 2′-[1, 2-Cyclohexanediylbis(nitriloethylidyne)] bis[4-bromophenol], CNBP, is synthesized through a Schiff base reaction applying the related ketone and diamine as the initiators. Four groups of six in each male SD rats are divided as negative group which are treated with gum acacia, positive control animals which are treated with topical dosage of Intrasite gel, and testing groups treated with low (10 mg/kg) and high (20 mg/kg) doses of CNBP. The excisional wounds are created on the posterior neck area of each group and the wound closure percentage was measured in the two separated days of the experiment. Moreover, the histopathological evaluation and determination of activities of superoxide dismutase (SOD), catalase (CAT), peroxidase (GPx), and malondialdehyde (MDA) of the skin sections are performed. Furthermore, the immunohistochemistry consists of the evaluation of Hsp70 and BAX proteins. Conclusions/significance: The wound closure percentage showed a significant increase in high dose CNBP-treated group compared to the negative control. Histopathological evaluation of the skin sections showed that granulation tissue contained more proliferating fibroblast, collagen deposition, angiogenesis, and also less inflammatory cells in the high dose CNBP-treated group compared to the normal rats. In the treated groups with CNBP, SOD, CAT, and GPx activities were found significantly higher, however, the MDA level was shown to be lower (*P < 0.05; **P < 0.01; ***P < 0.001) than the negative control. At the molecular level, CNBP (20 mg/ml, HD) improved wound-healing process via down and up regulation of Bax and Hsp70 protein, respectively at the wound site. © 2019